Crescimento e fotossíntese de clones de Coffea canephora em resposta à manipulação da relação fonte: dreno e disponibilidade de radiação - Viana, Flávia Nicácio (2016)
Brazil is now the world's largest coffee producer, and 20% of which corresponds to Coffea canephora species. However, knowledge of the physiological aspects of the species are still incipient. The purpose of this was working to evaluate the effect of manipulating the source relationship: drain on growth and photosynthesis of C. canephora clones grown in contrasting conditions of radiation availability. The experiment was conducted in a plantation located in Alegre-ES. We evaluated two clones (6V and 12V) belonging to the variety 'Victoria Incaper 8142'. Ten plants of each clone were selected, five remained under conditions of full sun and five were shaded with approximately 47%. Settling the following source relations: Drain the branches: with fruit / with girdling; with fruit / without annealing; unfruitful / with girdling and unfruitful / without annealing. Thus, we evaluated the growth of reproductive branches, the photosynthetic performance (gas exchange and chlorophyll a fluorescence) and leaf concentration of soluble total sugar, starch, soluble total phenol and chlorophyll and carotenoid. The factors studied showed independent responses. Clones showed different responses to radiation levels studied. The growth of branches was not affected by manipulating the supply relationship: drain. The clone 6V showed higher growth in the shade, while the clone 12v showed superior growth to full sun. Biomass partitions were significant to the source relationship: drain, without the fruitless branches had higher rates in the RAF and FMFo, translating into more enfolhados branches. For photosynthesis in clone 12v the value was kept constant and the stomatal conductance and transpiration showed lower values to full sun, resulting in greater efficiency of water use and easier to dissipate heat. The soluble sugar and starch fractions showed no significant difference to source relationship: drain or to radiation availability, these rates are affected in the short term only. For chlorophyll a / b ratio, the clone 12v showed higher values in full sun, resulting in improved heat dissipation efficiency.